Pengaruh model pembelajaran, status sosial ekonomi orang tua dan minat belajar terhadap prestasi belajar bahasa inggris siswa sekolah menengah pertama negeri di Kecamatan Gombong Kabupaten Kebumen tahun pelajaran 2014/2015 - Siti Rosiana (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to find out: there is the influence of the learning models, socio-economic status of parents and interest in learning the English language learning achievement of junior high school students in the District Gombong Kebumen regency Regency academic year 2014/2015. This research was conducted in junior high school in the district Gombong Kebumen district academic year 2014/2015. The sampling technique used is multi-stage cluster random sampling. Engineering data collection using questionnaires and test techniques. Analysis using Analysis of Variance (ANOVA) Line 3. Based on the results of this study concluded : (1) there is the significant positive effect of using learning model Think Pair and Share the learning achievement, (2) there is the significant positive effect of socioeconomic status of the parents of the use of learning model think Pair and Share the learning achievement of English, (3) there is the significant positive effect of interest in studying the influence of students' English learning achievement, and (4) there is the significant interaction effect of learning model use Think Pair and Share, socio-economic status of parents and interest in learning the English language learning achievement.